Interval between cytoreductions as a marker of tumor biology in selecting patients for repeat cytoreductive surgery with hyperthermic intraperitoneal chemotherapy. Issue 6 (12th June 2017) - Konstantinidis, Ioannis T.; Levine, Edward A.; Chouliaras, Konstantinos; Russell, Gregory; Shen, Perry; Votanopoulos, Konstantinos I.
Abstract : Background and Objectives: Repeat cytoreductive surgery with hyperthermic intraperitoneal chemotherapy (CRS/HIPEC) for recurrence of peritoneal surface malignancies is safe and effective. Patient selection and factors associated with a favorable outcome are still evolving. Methods: A prospectively maintained institutional database consisting of 1314 CRS/HIPEC procedures performed between February 1993 and December 2015 was reviewed. Clinicopathologic data from 103 patients and 112 (8.5%) repeat CRS/HIPEC procedures were retrospectively analyzed. Results: Primary tumors were appendiceal for 60 patients (58.3%), mesothelioma for 14 (13.6%), colorectal for 9 (8.7%), ovarian for 8 (7.8%). R0/R1 resection was achieved in 46 (46.5%) patients. The time interval between the initial and the repeat CRS/HIPEC was <1 year for 21 (20.4%), 1‐2 years for 40 (38.8%), and >2 years for 42 patients (40.8%). Overall median survival was 4.3 years and correlated with the time interval (1.3 years for <1 years, 3.7 years for 1‐2 years, and 7 years for >2 years; P < 0.001). In multivariate analysis, the R status ( P = 0.005) and a time interval of more than 2 years ( P = 0.0002) were strongly associated with survival with each additional month between the surgeries conferring a 2.6% reduction in the risk of death. Conclusions: The current series validates time interval between cytoreductions as a major surrogate of tumor biology in selection of patients with recurrent peritoneal surface malignancies for repeat CRS/HIPEC. Complete repeat cytoreduction more than 2 years from the initial surgery is associated with a favorable outcome.